(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: The study aims to design, fabricate and evaluate the performance of an automated smock (‘Fugu’) material Weaving Machine. Design/Methodology/Approach: The research employed a design-based experimental methodology aimed at modernising traditional smock (‘fugu’) weaving processes in Northern Ghana. The machine was built using locally available materials, including mild steel and wooden components, and powered by an electric motor. The design incorporated standard mechanical engineering formulas (e.g., torque, angular velocity, power output) for component dimensioning and force transmission. Observations were analysed comparatively using engineering principles and validated against findings from prior studies and relevant literature, reinforcing the scientific rigour of modifications made to address design limitations. Research Limitation: The ineffective shedding process, improper warp-shuttle synchronisation, and the short cam were the limitations observed. Findings: During the fabrication process, the treadles and the picking arms, which enhance the shedding and picking motions, respectively, experienced bending and twisting moments due to the material’s (i.e., ¾ square pipe) inability to withstand mechanical stress. All mechanisms demonstrate a continuous cycle with no requirements for human intervention, except to start the machine. Social Implications: Weaving has been a key aspect of Ghana’s cultural heritage; therefore, preserving the cultural significance of the art through the use of an automatic weaving machine is ensured. Practical Implications: The automatic smock (‘fugu’) material weaving machine employs key weaving processes, including beat-up, picking, shedding, let-off, and take-up motions, which utilise an electric motor to minimise manual intervention and enhance production speed. This implies that less human labour is required, thereby the smock material production increases within the shortest possible time with high efficiency. Originality/Value: The study presents a novel automated weaving machine designed explicitly for weaving local smock (‘fugu’) materials, which traditionally rely on manual looms. Finally, the machine features unique design innovations, such as camshaft-driven dual-picking systems, crankshaft-beater integration, and modified treadle reinforcement.